THE STYLISTIC ASPECT OF THE MEANING OF PHRASEOLOGICAL UNITS AS AN OBJECT OF MODERN LINGUISTIC THEORY - Nasirova Rano Azizovna (International Journal of Innovations in Engineering Research and Technology, 2021)
This article analyzes the units of phraseology and their major functions with examples which are complicated to understand. Besides, plenty of explanations of functions are stated here according to experienced scientists’ theories